2017
DOI: 10.1002/uog.17371
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of change in fetal cerebroplacental ratio in third trimester and risk of adverse pregnancy outcome

Abstract: Our results suggest that both the individual CPR Z-score and the magnitude and direction of change in CPR Z-score can identify pregnancies at risk of various adverse perinatal outcomes. However, the CPR Z-score at 35-37 weeks' gestation appears to be a better predictor. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Fetal Doppler assessment, particularly CPR ratio, is apparently useful for evaluating the wellbeing of AGA fetuses close to term. Recently, Flatley et al . found that CPR and change in CPR during the third trimester can identify pregnancies at risk of various adverse perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal Doppler assessment, particularly CPR ratio, is apparently useful for evaluating the wellbeing of AGA fetuses close to term. Recently, Flatley et al . found that CPR and change in CPR during the third trimester can identify pregnancies at risk of various adverse perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in antenatal care, the search for a test to identify the fetus at risk for intrauterine demise continues. The cerebroplacental ratio (CPR), a marker of brain sparing, is emerging as a predictor of adverse perinatal outcome, fetal growth restriction (FGR), neonatal care unit admission, intrapartum fetal compromise, episodes of recurrent reduced fetal movements, postnatal circulatory problems and perinatal death in near-term fetuses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Low CPR reflects redistribution of the cardiac output to the brain and has been shown to improve the accuracy of predicting adverse outcome, as compared with middle cerebral artery (MCA) or umbilical artery (UA) Doppler alone [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported by Triunfo et al 58 who showed that a low CPR in the third trimester of pregnancy had a higher association with adverse perinatal outcomes such as, nonreassuring fetal status requiring emergent cesarean section, 5-minute Apgar score <7, or neonatal metabolic acidosis at birth (UA pH ≤7.15 and base excess greater than 12 mEq/L) than EFW. These observations led to the evaluation of the CPR as a screening tool for pregnant women during the third trimester of pregnancy to identify fetuses at risk of late SGA, 5962 stillbirth, low pH in the umbilical cord, low Apgar scores, cesarean delivery for fetal distress, and admission to the neonatal intensive care unit. 6062 .…”
Section: Discussionmentioning
confidence: 99%
“…These observations led to the evaluation of the CPR as a screening tool for pregnant women during the third trimester of pregnancy to identify fetuses at risk of late SGA, 5962 stillbirth, low pH in the umbilical cord, low Apgar scores, cesarean delivery for fetal distress, and admission to the neonatal intensive care unit. 6062 .…”
Section: Discussionmentioning
confidence: 99%